2020
DOI: 10.1177/0886260520916844
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Sadism: Its Role in the Crime-Commission Process of Sexual Homicide of Children

Abstract: This study investigates the role of sexual sadism in the crime-commission process of sexual homicide (SH) involving child victims. A comparison between sadistic and nonsadistic cases involving child victims is conducted by examining the crime context, crime characteristics, methods of killing, body recovery characteristics, and forensic awareness strategies used by offenders. The sample comes from the Sexual Homicide International Database (SHIelD) including 135 cases of solved SHs involving child victims—35 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 63 publications
2
24
0
1
Order By: Relevance
“…As suggested in several studies, sadistic offenders do not target victims but were looking for specific situations allowing them to have an easier access to vulnerable victims (46,47).…”
Section: Sadisticmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested in several studies, sadistic offenders do not target victims but were looking for specific situations allowing them to have an easier access to vulnerable victims (46,47).…”
Section: Sadisticmentioning
confidence: 99%
“…Finally, we observed a difference in the method of killing. Juvenile sadistic SHOs were more likely to use weapons to kill their victims, whereas strangulation/asphyxiation has been identified as the most common method used by adult sadists (35,46,59,60).…”
Section: Sadisticmentioning
confidence: 99%
“…Victim characteristics. Previous studies found that SH of children is a heterogeneous crime with different categories of victims (i.e., age, sex) assaulted in various context (i.e., everyday activities, lifestyle) (Chopin & Beauregard, 2019c, 2020bLanning, 1994). We used a total of 12 dichotomous variables to describe the victim characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…There is no consistent method to operationalize what constitutes a child. In this study, we chose to follow guidelines provided by previous studies and therefore the current sample includes all cases involving victims under the age of 16 (see for example Beauregard et al, 2012;Chopin, 2017;Chopin & Beauregard, 2019c, 2020a, 2020bChopin & Caneppele, 2019;Leclerc et al, 2007;Leclerc et al, 2006;Leclerc et al, 2009;Leclerc et al, 2013;Leclerc et al, 2010Leclerc et al, , 2011Proulx et al, 2018). To be considered in this sample, there needed to be the presence of at least one of the following sexual behaviors: sexual penetration with a penis (i.e., vaginal and/or anal), fellatio, cunnilingus, penetration with fingers, masturbation, and inanimate object insertion.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation